Thermobarometry and geochemistry of peridotite xenoliths from the southwestern margin of the Kaapvaal craton, South Africa - Clark, Fiona (Department of Geological Sciences, 2022)
Globally, there are significant contrasts, both thermally and chemically, between peridotite xenoliths exhumed from Archean, and post-Archean terranes. Studies of the thermal structure of the lithosphere, in combination with surface heat flow data, suggest that thermal gradients beneath cratonic regions (Archean blocks which stabilized > 2.5 Ga) are lower than those in off-craton regions, commonly attributed to thinner lithosphere in Proterozoic domains. Although this is true to an extent for southern Africa, the contrasts appear less distinct than Archean-Proterozoic lithosphere contrasts elsewhere, and the thermal structure reflects a regional, Mesozoic, disturbances which has been temporally linked to large-scale tectonic processes. Major element P-T results from peridotite xenoliths sampled during Group II kimberlite magmatism (~ 150 Ma), that erupted through the southwestern Proterozoic NamaquaNatal Province record geothermal gradients akin to those of cratonic terranes. In contrast, xenoliths sampled during the younger Group I kimberlite magmatism (~ 80 Ma) within the Namaqua-Natal Province record equilibration temperatures which are displaced to higher values throughout the pressure ranges. This study reports results from peridotite xenolith samples from seven kimberlites and related rocks which erupted within the Eastern Namaqualand and Namaqualand-Bushmanland-Warmbad area. Two of the localities studied here (Melton Wold and Markt) erupted during Group II kimberlite magmatism, and five localities (Hebron, Uintjiesberg, Gansfontein, Hoedkop and Schuitdrift) erupted during the younger Group I kimberlite magmatism. The results build on prior work, which focused on mineral and whole rock major element chemistry, platinum group elements and Re-Os isotope data, and provide an insight into lithosphere formation and modification in the Namaqua-Natal lithospheric mantle through mineral trace element analysis. These samples also provide an opportunity to further investigate the Mesozoic thermal evolution of the NamaquaNatal lithosphere through application of a REE-based thermobarometer. REE diffusion rates are typically 2 – 3 orders of magnitude lower than divalent major elements, making the REE-based thermobarometer a potentially useful tool for probing the contrasting thermal profiles exhibited in samples from the Group II and Group I kimberlites studied here. Major element-based thermobarometry results and the resulting FITPLOT paleogeotherms indicate that at the time of Grp II kimberlite magmatism the Namaqua-Natal lithosphere was ~ 200 km thick, with a 60 km “diamond window”, and had a geothermal gradient of 40 mW/m2 . In contrast, at the time of Grp I kimberlite magmatism ~ 60 km of lithospheric erosion may have occurred, accompanied by a shift in the thermal regime of the Namaqua-Natal lithosphere to a 45 mW/m2 geotherm. REE-based thermobarometry results produce a large amount of scatter in P-T space, even after a rigorous attempt at identifying well equilibrated clinopyroxene and garnet pairs. The presence of carbonatitic and silico-carbonate metasomatic signatures in these samples necessitates caution in the use of the REE-based thermobarometer when applied to xenoliths entrained by kimberlites. It is likely that the scatter observed in the results presented here is due to differing REE partitioning controls in systems containing carbonate in the melt to those of carbonate-free, silicate melts. HREE concentration in reconstructed whole-rocks and olivine Mg-numbers are consistent with 30% melt extraction in a shallow melting regime. Garnet and clinopyroxene trace element signatures indicate a shift in the style of metasomatism in the Namaqua-Natal lithosphere between Group II and Group I kimberlite magmatism. Zr/Hf versus Ti/Eu systematics reflect kimberlitic/silicate style metasomatism in the samples exhumed during Group II magmatism, whereas samples exhumed during Group I kimberlite magmatism reflect a carbonatitic style of metasomatism.